Znaczenie finansów samorządów terytorialnych w tworzeniu pozycji konkurencyjnej - Bal-Domańska, Beata (The importance of local self-government units' finances in creating their competitive position, 2005)
The process of competing may take place on many levels and by means of many tools. The objective of this article is to present the importance of local selfgovernment units’ finances in creating their competitive position. Through their financial system both regions and local units have an opportunity of shaping their competitive advantage in an active way in relation to other structures. Apart from that the article also describes financial situation of local self-government units, following the enforcement of new legislation, regarding local self-governments’ financing, as well as the consequences of these changes for the possibility of creating their competitive position.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 84-95